[Application of microwave-assisted extraction coupled with dispersive liquid-liquid microextraction for the determination of polycyclic aromatic hydrocarbons in vegetables, Aplikasi pengekstrakan berbantukan mikrogelombang gandingan dengan pengekstrakan mikro cecair-cecair serakan bagi penentukan hidrokarbon aromatik polisiklik dalam sayur-sayuran] - Chai, Mee Kin; Tan, Yeong Hwang; Wong, Ling Shing (The Malaysian Analytical Sciences Society, 2020)
Microwave-assisted extraction (MAE) coupled with dispersive liquid-liquid microextraction (DLLME) followed by gaschromatography flame ionization detector (GC-FID) for the determination of 13 PAHs in vegetable samples was developed in this study. The analytical performances of the optimized DLLME and MAE-DLLME including limit of detection (LOD), limit of quantification (LOQ), precision, accuracy, relative extraction recovery and relative extraction factor were validated and compared. The LOD of DLLME and MAE-DLLME were in the range of 0.040-0.400 and 0.0200-0.080 µg/L, respectively. For DLLME, precision and accuracy were 1.22-7.50% (RSD) and 71.77% to 90.93%, respectively; while for MAE-DLLME, were 0.77%-3.07% (RSD) and 83.65-98.42%, respectively. The relative extraction recovery was improved from 70.81% – 85.41% in DLLME to 85.79% - 99.61% in MAE-DLLME. The relative enrichment factors were ranged from 126-156 and 165 to 202 for DLLME and MAE-DLLME, respectively. The volume of extraction solvent was reduced from 50 µL to 30 µL in MAEDLLME. The overall analytical performances of MAE-DLLME is better than DLLME. The application of proposed MAEDLLME in real samples was also investigated and discussed.